Charity Density and Social Need: A Longitudinal Perspective. (October 2020) - McDonnell, Diarmuid; Mohan, John; Norman, Paul
The distribution of charitable organizations in an equitable and socially just manner is a long-standing policy concern in the United Kingdom and many other jurisdictions. Geographic variations are important as they are linked to potentially inequitable service provision and opportunities for participation in voluntary activities. This study links large-scale administrative data on charities registered in England and Wales with local authority-level measures of material deprivation for 5 U.K. census years (1971–2011). Count and spatial regression models show evidence of nonlinear associations between charity density and social need, and changes in the shape of this distribution over time. In general, charity density is highest in the least deprived local authorities but this varies across different types of organizations and census years. These results provide important new insights into the evolving relationship between charity density and social need, and demonstrate the value of adopting more advanced, longitudinal statistical approaches for studying this phenomenon.